Faktor-faktor yang Mempengaruhi Efektivitas Kerja Dinas Pengelolaan Keuangan dan Aset Daerah (DPKAD) Kota Semarang dalam Penarikan Pajak Reklame di Kota Semarang - Nasa, Engelbertus; Suryaningsih, Margaretha; Subowo, Ari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Achievement of Organization Direction Attainment on Regional Asset andÂ Financial Management Agency (RAFMA) of Semarang City in advertisement taxÂ collection, become the backround of this research. Purpose of this research wereÂ giving contribution and increasing Local Revenue. The problem that happen how wasÂ work effectiveness on RAFMA in advertisement tax collection on Semarang City?Â Purpose of this research was to conceiving and analyzing RAFMA effectiveness inÂ advertisement tax collection on Semarang City, based on Factors that affecting theÂ implementation.An attempt to answer the problem and research objectives is done by usingÂ the theory of measuring the effectiveness of the Organization as well as theÂ effectiveness of contributor criteria as factors that affect the organization. The objectÂ of research is the field of tax areas are located in Regional Asset and FinancialÂ Management Agency (RAFMA) of Semarang City.The result showed that RAFMA of Semarang City â€œis not effectiveâ€, in a bidÂ to accomplishment of an objective related to tax collection ads in semarang city. It isÂ affected by factors such as a shortage of employees and equipment, the division ofÂ work is too obvious, which has not been service system still complicated, the absenceÂ of a valid about the amount of data ads in the city of semarang, and the problem ofÂ the low public awareness to pay the tax billboard.Advised to RAFMA of Semarang City acted more innovative and active byÂ sending through the other media, as a magazine, radio, or website belonging to theÂ department. Centralizing budget for facilities and infrastructures are lacking.Â Cooperate with dinas-dinas related for collecting data reÃ«xamined against adsÂ spread in city semarang.Repair service system using â€œOne Stop Service (OSS)Â Systemâ€ system or one roof service system.